Vitamin D on the susceptibility of gestational diabetes mellitus: a mini-review - Zhang, Ting; Yang, Lan; Yang, Shuman; Gao, Song (Frontiers in Nutrition, 2025)
Gestational diabetes mellitus (GDM), which refers to diabetes mellitus or abnormal glucose tolerance of any degree occurring during pregnancy, is a distinct type within the diabetes classification. 25-hydroxyvitamin D deficiency has been associated with an increased risk of maternal glycaemia, insulin resistance and gestational diabetes. There is no consensus on the definition of vitamin D deficiency, but most scientists define vitamin D deficiency as less than 20 ng/mL (50 nmoL/L) of 25-hydroxyvitamin D. Vitamin D deficiency is common in women during pregnancy. Vitamin D can regulate the course of gestational diabetes, which may be related to regulation of insulin gene transcription, insulin secretion, intracellular and cytosolic calcium balance, inhibition of oxidative stress and inflammatory responses and alteration of glucose metabolism. This is a review article that aims to analyze the possible mechanism of vitamin D regulation of GDM, which provides a theoretical basis for clinical researchers in the future management of patients with GDM.